Inclusion of children with cerebral palsy in basic education (Fisioterapia e Pesquisa, 2014)
The aim of the study was to analyze the inclusion of children with cerebral palsy in elementary schools. The sample consisted of 31 children between 1 and 11 years old, with a mean of 5 years and 2 months, coming from 2 rehabilitation centers and their leaders and teachers. As for functionality, 71% are Gross Motor Function Classification System (GMFCS) level I, 51.6% are diplegic and 58.1% had cerebral palsy during the prenatal stage. Regarding economic classification, 54.8% of the families were in class C. A neurological evaluation form was applied. A gross motor evaluation using the GMFCS; a socioeconomic assessment using the Brazilian Criteria for Economic Classification and the School Function Assessment were done. The results revealed that these children perform their activities in all aspects of the school participation, although they require constant supervision, moderate assistance and minimal adaptation. These results may be useful to better adapt the school environment, for a better targeting of assistance provided and to plan clinical interventions with these children.